Theodore Roosevelt papers - Roosevelt, Theodore, 1858-1919.
Correspondence, diaries, speeches, articles, executive orders, family papers, press releases and proclamations, scrapbooks, and other material relating to the political, social, and cultural history of Roosevelt's life and presidency. Documents Roosevelt's service as U.S. civil service commissioner, New York City police commissioner, governor of New York, and vice president and president of the United States as well as his career after leaving the White House. Among the family papers are letters and memorabilia of his sons, Archibald B. Roosevelt and Quentin Roosevelt, and other family members.
Correspondents include Lyman Abbott, Albert Jeremiah Beveridge, William Sturgis Bigelow, Joseph Bucklin Bishop, Charles J. Bonaparte, Robert Bridges, Viscount James Bryce, John Burroughs, Nicholas Murray Butler, Andrew Carnegie, Henry Clark Corbin, George B. Cortelyou, William Dudley Foulke, James Rudolph Garfield, Hamlin Garland, Richard Watson Gilder, Marcus Alonzo Hanna, John Hay, J. J. Jusserand, Philander C. Knox, Christopher La Farge, Henry Cabot Lodge, Seth Low, A. T. Mahan, Medill McCormick, William McKinley, William H. Moody, Benjamin B. Odell, John Callan O'Laughlin, Endicott Peabody, George W. Perkins, Gifford Pinchot, Thomas Collier Platt, Whitelaw Reid, Jacob A. Riis, Elihu Root, William W. Sewell, Albert Shaw, Sir Cecil Spring Rice, Baron Hermann Speck von Sternburg, William H. Taft, Sir George Otto Trevelyan, George Sylvester Viereck, Booker T. Washington, Benjamin Ide Wheeler, William Allen White, John Willis, Owen Wister, and Leonard Wood.
Microfilm edition of the William L. Day letters available
Microfilm edition of series 1-15 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
President and vice president of the United States, U.S. civil service commissioner, governor of New York, author, and conservationist.
Keywords: Abbott, Lyman, -- 1835-1922 -- Correspondence; Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Bigelow, William Sturgis, -- 1850-1926 -- Correspondence; Bishop, Joseph Bucklin, -- 1847-1928 -- Correspondence; Bonaparte, Charles J. -- 1851-1921 -- Correspondence; Bridges, Robert, -- 1858-1941 -- Correspondence; Bryce, James Bryce, -- Viscount, -- 1838-1922 -- Correspondence; Burroughs, John, -- 1837-1921 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Corbin, Henry Clark, -- 1842-1909 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Foulke, William Dudley, -- 1848-1935 -- Correspondence; Garfield, James Rudolph, -- 1865-1950 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; La Farge, Christopher, -- 1897-1956 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Low, Seth, -- 1850-1916 -- Correspondence; Mahan, A. T. -- 1840-1914 -- Correspondence; McCormick, Medill, -- 1877-1925 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Moody, William H. -- 1853-1917 -- Correspondence; Odell, Benjamin B. -- 1854-1926 -- Correspondence; O'Laughlin, John Callan, -- 1873-1949 -- Correspondence; Peabody, Endicott, -- 1857-1944 -- Correspondence; Perkins, George W. -- 1862-1920 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Riis, Jacob A. -- 1849-1914 -- Correspondence; Roosevelt, Archibald B. -- 1894-1979 -- Correspondence; Roosevelt, Quentin, -- 1897-1918 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Sewell, William W. -- Correspondence; Shaw, Albert, -- 1857-1947 -- Correspondence; Spring Rice, Cecil, -- Sir, -- 1859-1918 -- Correspondence; Sternburg, Hermann Speck von, -- Freiherr, -- 1852-1908 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Trevelyan, George Otto, -- 1838-1928 -- Correspondence; Viereck, George Sylvester, -- 1884-1962 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; Wheeler, Benjamin Ide, -- 1854-1927 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Willis, John, -- 1857-1944 -- Correspondence; Wister, Owen, -- 1860-1938 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Roosevelt family; Roosevelt family -- Correspondence; United States. -- Civil Service Commission; Police administration -- New York (State) -- New York -- History -- 19th century; New York (State) -- Politics and government; United States -- Politics and government -- 1897-1901.; United States -- Politics and government -- 1901-1909.; United States -- Politics and government -- 20th century; United States -- Social life and customs -- 1918-1945.